IBN HAZM DAN MADZHAB AZH-ZHAHIRI - Aripin, Jaenal (ALQALAM, 2010)
Ibn Hazm (Abenhazam de Cordoba)'s thought has an important position in the study of Islamic law philosophy, especially dealing with his three main thoughts: differentiation between God and His creature dimensions, thoroughfulness of syari'a so that it is uncorrect to argue in the name of religion by using premises out of the texts, and the importance of language as a tool to understand the God's massages. Based on his thoughts, Ibn Hazm plays a unique position in the discourse of Islamic thoughts. On the one hand, his thoughts are philosophical, on the other hand, he is a textualistic and normative Zhahirianist. Hene, he is frequently called a philosopher who remains thinking normatively. Keywords: Literalisme, Mazhab, Ibnu Hazm, Azh-Zhahiri.